Early emotional and behavioural problems predict use of habilitation services among children: Findings from a longitudinal follow-up study - Ashok, Pavithra; Fäldt, Anna; Dahlberg, Anton; Durbeej, Natalie (PloS one, 2024)
To explore the association between early emotional and behavioural problems and use of habilitation services among children in Sweden. In this longitudinal cohort study, we used data on children, 3-5 years of age, whose mothers (n = 7343) and fathers (n = 6322) had responded to the Strengths and Difficulties Questionnaire (SDQ) for assessment of emotional and behavioural problems, and who were followed for approximately 6.5 years with regard to use of habilitation services. The relations between emotional and behavioural problems and use of habilitation services were explored through cox regression models. In unadjusted models, children with identified emotional and behavioural problems were more likely to utilise habilitation services compared to those with no identified problems. These associations were shown for both mothers' (HR: 5.02) and fathers' (HR: 4.25) SDQ ratings. In adjusted cox-regression models, the associations remained significant for both mothers' (AHR: 4.24) and fathers' (AHR: 4.03) ratings. Early emotional and behavioural problems predict later habilitation service use among children in Sweden. Assessment of these problems in all children at child health services could facilitate early identification and timely interventions. Habilitation centres in Sweden could integrate mental health care into the standard treatment for children using these services.